Handbook on nondestructive testing of concrete - Malhotra, V. M.; Carino, Nicholas J. (CRC Press, 2004)
Civil and structural engineering consultants engaged in quality control or investigations of hardened concrete need a comprehensive resource that explains the methods of determining strength and other performance characteristics. The Handbook examines the tools and techniques used to estimate the in-place strength of concrete and permeation properties that relate to potential durability, and it also describes the methods used to assess the condition of concrete integrity and steel reinforcement. The chapters discuss the basic principles of the methods and offer practical guidance for their use. Extensive mathematical derivations are kept to a minimum; instead, the Handbook refers to numerous original papers for those interested in more detailed information.